Up, Down, and All Around: Diagnosis and Treatment of Novel STAT3 Variant - Weinreich, Michael Alexander; Vogel, Tiphanie P.; Rao, V. Koneti; Milner, Joshua D. (Frontiers in Pediatrics, 2017)
The number of identified monogenic causes of childhood-onset autoimmunity due to nodal and extranodal lymphoproliferation has increased. These pathogenic genetic variants provide the potential for pathway-specific treatment. Novel variants also require pathway-specific verification. In this report we describe 14-year-old patient with a novel variant in STAT3. We report clinical and laboratory findings that support STAT3 p.G419R as a novel pathogenic STAT3 GOF variant.